Asosiasi Gastropoda dengan Padang Lamun di Pantai Geger, Nusa Dua, Bali - Sidik, Awalul Rizal Rohman; Indrawan, Gede Surya; Atmaja, Putu Satya Pratama (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The Nusa Dua coast is an area that has a diverse ecosystem, ranging from coral reefs, mangrove forests and seagrass beds. Seagrass beds themselves play an important role in marine ecosystems and are used as shelter, foraging areas and spawning grounds for animals that live in seagrass habitats, one of which is gastropods. Gastropods have an important role in aquatic ecosystems, namely helping in the process of mechanical decomposition of organic material through their feeding activity, which will then be used by seagrass plants to carry out photosynthesis to support the growth of seagrass. The aim of this research is to analyze the community structure of Gastropods and to analyze the association between Gastropods and seagrass in the waters of Geger Beach, Nusa Dua, Bali. Samples were taken from 3 stations, station 1 was in a location next to a rocky road, station 2 was in a location where there were many fishing boats, and station 3 was in a location where there were no fishing boats. In the waters of Geger Beach, 5 types of seagrass species were found consisting of Thalassia hemprichii, Enhalus acoroides, Cymodocea rotundata, Halophilla ovalis, and Syringodium isoetifolium. At Geger Beach, 25 families, 76 species and 276 individuals were obtained of gastropods, with a diversity (H') value of 2.10, uniformity (E) of 0.59, and dominance (D) of 0.19. These results indicate that the Gastropod structure at Geger Beach is in a stable condition. The association between Gastropods and seagrass beds is dominated by associations with a very low category, which has an association value of <0.22 for 295 species. This is thought to be due to the low number of species appearing and the existence of competition between the two species at the observation location.